ACOUSTICAL AND THERMODYNAMICAL PROPERTIES OFPOTASSIUM FERRICYANIDE AND POTASSIUM FERROCYANIDEIN CHITOSAN SOLUTIONS AT 298.15K - D. MOHARATHA; M. TALUKDAR; G. S. ROY; U. N.DASH (International Journal of Pharma and Bio Sciences, 2013)
The nature and relative strength of the intermolecular interaction between the components of the liquid mixtures have been successfully investigated by the ultrasonic velocity (U), density (d) and viscosity (η) measurements for potassium ferricyanide and potassium ferrocyanide in chitosan solutions in different concentrations at 298.15K. Experimental data have been used to estimate the isentropic compressibility (Ks), apparent molar volume (VÑ„), limiting apparent molar isentropic compressibility (Ks,Ñ„), and acoustic impedance. The variation of these parameters has been discussed in the light of solute-solvent and solute-solute interactions. The viscosity data have been analysed on the basis of Jones-Dole equation to interpret the ion-solvent interaction for which Jones-Dole coefficients, AF and BJ have also been determined.